Theoretical studies of the local structures and spin Hamiltonian parameters for Cu2+ in alkaline earth alumino borate glasses - Guo, Jia-Xing; Wu, Shao-Yi; Kuang, Min-Quan; Peng, Li; Wu, Li-Na (Modern physics letters. B, Condensed matter physics, statistical physics, applied physics, 2018)
The local structures and spin Hamiltonian parameters are theoretically studied for Cu 2 + in alkaline earth alumino borate (XAB, X = Mg, Ca and Sr) glasses by using the perturbation calculations for tetragonally elongated octahedral 3d9 groups. The [ CuO 6 ] 1 0 − groups are subject to the large relative tetragonal elongation ratios of 15.4%, 13.4% and 13.0% for MgAB, CaAB and SrAB glasses, respectively, arising from the Jahn–Teller effect. The decreasing cubic field parameter Dq, orbital reduction factor k and relative elongation ratio with the increase of the radius of alkaline earth ion X from Mg to Ca or Sr are analyzed for the studied systems in a uniform way.